Effect of Heat Stress on Sperm Production, Oxidative Markers and their Association in Native Breeding Bulls - Dhami, Arjun J; Suthar, Vishal S; Chaudhari, Dinesh V; Hadiya, Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The objective of the study was to evaluate the effect of climatic conditions on fortnightly semen quality and its oxidative markers, andto evaluate the correlation between them in zebu cattle and buffalo breeding bulls under weekly twice semen collection schedule. Themacro- (observatory; daily; n=330) and micro- (bull shed; hourly; n=8540) climatic parameters, viz., ambient temperature (AT °C) andrelative humidity (RH %) were measured during Jan to Dec 2018 and temperature humidity index (THI) was generated. There were highassociations between micro and macro AT (r=0.982), RH (r=0.897) and THI (r=0.985). Overall, micro-AT was 1.20°C higher, micro-RH was5.42% lower and the micro-THI was 0.50 higher than the corresponding macro-climatic parameters. Therefore effect of micro-climaticAT, RH and THI was evaluated on biweekly collected 26 ejaculates of three bulls each of Surti, Murrah buffalo and Gir cattle breeds.The macro and microscopic parameters of semen and oxidative markers in seminal plasma, viz., catalase, lipid peroxidation (MDA),superoxide dismutase (SOD) and glutathione peroxidase (GPx) were determined. During the day 72.6% of hours, bulls experiencedstress (THI > 72). No impact of season was observed on seminal attributes and oxidative markers of cattle and buffalo bulls, howevercorrelation coefficients were achieved. The results of our study warrants further investigation on more number of bulls including theirsemen freezability and fertility
Keywords: Native; Bull; , Macro-micro-climate; Oxidative markers; Semen production; Tropics